?SYNTHESIS OF SOME NEW PYRAZOLINES FROM 4-AMINO-4-METHOXYBENZALACE- TOPHENONE AS DYESTUFFS INTERMEDIATES - SAYED, A. Z.; EMAN, H. A.; SELIM, M. R. (Biological Sciences - PJSIR, 1996)
New aminopyrazo1ine derivatives (II-V) has been obtained by the reaction of new benzalacetophenone deriva- tives (Ia, b) with hydrazine hydrate and their derivatives. Further reactions were carried out on pyrazolines (VI-XI). The structural determination of the prepared compounds has been confirmed using elemental analysis, chemical reac- tions and spectral data.